Salafi Movement Post-Conflict Ambon: A Search for Identity in Maluku - Toisuta, Hasbollah; Ernas, Saidin; Wakano, Abidin (Journal of Al-Tamaddun, 2023)
This article provides an overview of the development of contemporary Salafi movements in Maluku following the 1999 conflicts. The emergence and spread of the Salafi movement in this region has been significant over the past two decades, extending throughout Muslim communities in Maluku. This article explores the origins and connections between the Salafi movements in Maluku and nationwide and examines how local Muslims have responded to these developments. Through qualitative analysis using descriptive methods, data was collected through observations and interviews with key figures from both within the Salafi community and local community leaders. The findings show that the presence of the Salafi movements in Maluku is notable, particularly through their involvement in education and politics (da’wah). These movements can be characterised as purist while also encompassing educational, social, and political dimensions within Malukan society. The multifaceted approaches employed by this group have contributed to its growing acceptance among local Muslims.